Raziskovalno-razvojna vlaganja kot osnova za tehnološki razvoj v Sloveniji - Stanovnik, Peter (Mednarodno inovativno poslovanje, 2019)
In this article, we discuss the research and development (R&D) as one of the key determinants that promote innovation, technological development and, indirectly, economic growth and the competitiveness of economies and businesses. International comparisons at the macroeconomic level over the past 17 years show a slow rise in the coefficient (ratios) between R&D expenditures and GDP. In the most advanced economies, the share of R&D expenditure is approaching or even exceeding 3% of GDP. Slovenia is one of the countries that did not reach the OECD average, which stood at 2.3% of GDP in 2016. In the period 2013-2017, a negative trend in R&D expenditures in Slovenia was established for variousreasons (change in R&D recording, tax relief, economic conjuncture). In a very small proportion of targeted applied research and experimental development, we can search for the causes of technological backlogs in the Slovenian economy.
Keywords: raziskovalno-razvojna dejavnost; research and development; Slovenia; Slovenija; structure of R&D expenditures; struktura RR izdatkov; technological development; tehnološki razvoj